The crystal structure of (4-fluorophenyl)(5-(hydroxymethyl)furan-2-yl)methanol, C12H11FO3 - Gao Yanrong; Ran Hui; Tang Wenqiang (Zeitschrift für Kristallographie - New Crystal Structures)
C12H11FO3, monoclinic, P21/c (no. 14), a = 12.0648(9) Å, b = 8.3896(5) Å, c = 10.5727(9) Å, β = 104.204(8)°, V = 1037.44(14) Å3, Z = 4, R gt(F) = 0.0614, wR ref(F 2) = 0.1516, T = 293 K.